(untitled) (Chittagong University Journal of Biological Sciences, 2024)
Plant resources have been utilized since ancient times for the healing of various illnesses of humankind. This study investigated the secondary metabolites, antibacterial, and antioxidative capability of Paederia foetida L. (P. foetida) leaf extract. Qualitative tests were done to determine the presence of secondary metabolites. The disc diffusion method was used for the determination of the antibacterial activity of the extract. The DPPH (1, 1-diphenyl-2-picrylhydrazyl) free radical scavenging assay, reducing power assay, total phenolic, and total flavonoid content methods were followed for the evaluation of antioxidative potentials of the leaf extract. The leaf extract was found to show significant (p < 0.05) antibacterial activity against Gram-positive bacteria compared to Gram-negative ones. In DPPH free radical scavenging assay, the inhibitory concentration (IC50) value for methanol crude extract was found to be fairly significant (162.929 μg/mL) in comparison with that (1.57 µg/mL) of the reference standard ascorbic acid. The maximum absorbance for reducing power assay was 0.823 compared to 1.891 for standard ascorbic acid. The extract was found to have a total phenolic content of 8.03 ±1. 05 mg/g gallic acid equivalent and flavonoid content 134.74 mg/g quercetin equivalent. The results demonstrated a moderate antibacterial and promising antioxidative activity of P. foetida leaf extract, but it is necessary to further analyze prospective pharmaceutical preparation. The Chittagong Univ. J. B. Sci.,Vol. 10(1 &2):121-137, 2020